Influence of tectonic inversion and salt mobility on structural styles and reservoir quality in the Norwegian Central Trough - Sawyer, Steven Richard Frank (The University of Edinburgh, 2010)
Tectonic inversion and halokinesis are well documented as mechanisms for generating structural traps for hydrocarbons. Many sedimentary basins that contain kinematically active halite deposits have also experienced deformation related to positive tectonic inversion (contractional reactivation of pre-existing structures). In such cases, patterns of uplift are often complex and the relative role of competing deformation processes and their influence on structural style is poorly understood.

The focus for this study is the Norwegian sector of the Central North Sea. A major petroleum play comprises Chalk Group reservoirs, where trap development has previously been attributed to halokinesis of the Permian Zechstein Supergroup, to Mesozoic and Cenozoic tectonic inversion events, and to a combination of both, but has never been well understood. Interpretation of high resolution 3D seismic data from a 5000 km2 area has revealed new insights into the relationship between tectonic inversion and halokinesis.

Halite of the Zechstein Supergroup became mobile during the Triassic, with the creation of minibasins and adjacent salt highs. Salt movements continued until Miocene times. Tectonic inversion was driven by far-field plate margin forces and occurred during comparatively discrete intervals; the principal events are dated Maastrichtian - Danian (contemporaneous with Chalk deposition) and Eocene - Middle Miocene. The timing and extent of salt movement prior to inversion is a major control on structural style associated with that inversion; there are consistent and predictable differences between salt-free areas as opposed to salt-prone areas. Where there is no salt (or salt has been expelled) structural styles are deep-seated, more asymmetric and localized over the site of a pre-existing structural trend.

Tectonic inversion and halokinesis have affected the porosity and permeability characteristics, and therefore the reservoir quality, of the Upper Cretaceous Chalk Group. Syn-depositional uplift exerted a strong influence over Chalk Group thickness distribution and depositional facies type. Sedimentological studies suggest initial (facies-related) matrix porosity variations were preserved or even enhanced during subsequent diagenesis.

The physical characteristics of internal fracturing are a major control over Chalk Group reservoir quality. Historically, it has been difficult to characterize sub-seismic scale 3D heterogeneities within the Chalk Group. This study has addressed the problem of fracture development in response to fold growth through integration of theoretical considerations, subsurface data and outcrop observations, using suitably chosen structural analogues. It is probable that both inversion and halokinesis directly affected and enhanced the fracture characteristics of the reservoir.